(untitled) (Perner’s Contacts, 2011)
The submitted text deals with the comparison of results and usability of linear programming methods aimed at designing the signal plans of traffic light controlled intersections. The usability is being assessed via computational experiments in circumstances of a larger-scale intersection. Decomposition approach and exact approach were assessed. In most cases, the exact approach showed better results; in the process, it is not so time-demanding for preparation of data as well. However, its disadvantage is high computer technology performance requirements which projects also to the economical point of view.